Integrative Analyses of mRNA Expression Profile Reveal SOCS2 and CISH Play Important Roles in GHR Mutation-Induced Excessive Abdominal Fat Deposition in the Sex-Linked Dwarf Chicken - Chen, Genghua; Chen, Jiahui; Wu, Jingwen; Ren, Xueyi; Li, Limin; Lu, Shiyi; Cheng, Tian; Tan, Liangtian; Liu, Manqing; Luo, Qingbin; Liang, Shaodong; Nie, Qinghua; et al. (Frontiers in Genetics, 2021)
Sex-linked dwarf (SLD) chicken which is caused by a recessive mutation of the growth hormone receptor (GHR) has been widely used in the Chinese broiler industry. However, it has been found that the SLD chicken has more abdominal fat deposition than normal chicken. Excessive fat deposition not only reduced the carcass quality of the broilers, but also reduced the immunity of broilers to diseases. To find out the key genes and the precise regulatory pathways that involved in the GHR mutation-induced excessive fat deposition, we used high-fat diet and normal diet to fed the SLD chicken and normal chicken and analyzed the differentially expressed genes (DEGs) among the four groups. Results showed that the SLD chicken had more abdominal fat deposition and larger adipocytes size than normal chicken, and high-fat diet can promote abdominal fat deposition and induce adipocyte hypertrophy. RNA-sequencing results of the livers and abdominal fats from the above chickens revealed that many DEGs between the SLD and normal chickens were enriched in fat metabolic pathways, such as PPAR signaling, ECM-receptor pathway, and fatty acid metabolism. Importantly, by constructing and analyzing the GHR-downstream regulatory network, we found that suppressor of cytokine signaling 2 (SOCS2) and cytokine inducible SH2 containing protein (CISH) may involve in the GHR mutation-induced abdominal fat deposition in chicken. The ectopic expression of SOCS2 and CISH in liver-related cell line leghorn strain M chicken hepatoma cell and immortalized chicken preadipocytes revealed that these two genes can regulate fatty acid metabolism, adipocyte differentiation, and lipid droplet accumulation. Notably, overexpression of SOCS2 and CISH can rescue the hyperactive lipid metabolism and excessive lipid droplet accumulation of primary liver cell and preadipocyte which isolated from the SLD chicken. This study found some genes and pathways involved in abdominal fat deposition of the SLD chicken, and reveals that SOCS2 and CISH are two key genes involved in the GHR mutation-induced excessive fat deposition of the SLD chicken.